TLC-fingerprinting and chemometrics for identification of Curcuma xanthorrhiza from different geographical origins in Indonesia - KARTINI KARTINI; SYAHNA S. SABATINI; NINDYA M. HARIDSA; NIKMATUL I. E. JAYANI; FINNA SETIAWAN; MOCHAMMAD A. HADIYAT (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kartini K, Sabatini SS, Haridsa NM, Jayani NIE, Setiawan F, Hadiyat MA. 2023. TLC-fingerprinting and chemometrics for identification of Curcuma xanthorrhiza from different geographical origins in Indonesia. Biodiversitas 24: 6557-6566. Geographical origin is an important parameter that influences the quality of herbal medicine. The fingerprint of herbal plants is expressed as chemical compounds contributing to said quality. Curcuma xanthorrhiza, popular as java turmeric, is extensively used in Indonesian traditional medicine. This study aimed to validate and develop a Thin Layer Chromatography (TLC) fingerprint of C. xanthorrhiza, followed by chemometric techniques to classify C. xanthorrhiza rhizomes from 15 regions in Indonesia. Under selected TLC conditions (i.e., stationary phase: TLC plate Silica gel 60 GF254, mobile phase: dichloromethane, chloroform, and ethanol (10: 10: 1), detection: vanillin-sulfuric acid reagent), C. xanthorrhiza produced five zones of the compound. Extracts were stable both on the TLC plate and in the extract solution during chromatography and within 60 minutes after derivatization. In terms of precision, the chromatogram meets the requirement of intraday precision. Chemometric analysis with Principal Component Analysis (PCA) and Cluster Analysis (CA) showed that the samples of C. xanthorrhiza from 15 regions in Indonesia were grouped into five clusters based on the similarity of the chemical compounds, namely cluster 1 (Tawangmangu, Bangkalan, Kediri, and Surabaya); cluster 2 (Batu, Sragen, Tulungagung, Pasuruan, Blitar, and Lombok Tengah); cluster 3 (Ngawi); cluster 4 (Gresik); and cluster 5 (Bojonegoro, Banyuwangi, and Palangkaraya). The TLC fingerprinting with chemometrics on C. xanthorrhiza rhizome is useful for quality control based on geographic origin and authenticity identification.